Nanoparticles and Inflammation - Ross Stevenson; Axel J. Hueber; Alan Hutton; Iain B. McInnes; Duncan Graham (The Scientific World Journal)
The development of nanoscale molecular probes capable of diagnosis, characterization, and clinical treatment of disease is leading to a new generation of imaging technologies. Such probes are particularly relevant to inflammation, where the detection of subclinical, early disease states could facilitate speedier detection that could yield enhanced, tailored therapies. Nanoparticles offer robust platforms capable of sensitive detection, and early research has indicated their suitability for the detection of vascular activation and cellular recruitment at subclinical levels. This suggests that nanoparticle techniques may provide excellent biomarkers for the diagnosis and progression of inflammatory diseases with magnetic resonance imaging (MRI), fluorescent quantum dots (QDs), and surface enhanced Raman scattering (SERS) probes being just some of the new methodologies employed. Development of these techniques could lead to a range of sensitive probes capable of ultrasensitive, localized detection of inflammation. This article will discuss the merits of each approach, with a general overview to their applicability in inflammatory diseases.